Environment to the legal definition of natural resources and its relationship with the constitutional and fundamental right to enjoy a balanced and adequate environment - Juan José Romero Anguerry (2019)
The legal study of natural resources should start, among others, the analysis of the legal definition of them established in Law No. 26821. This definition presents successes and deficiencies, which are intended to reveal and analyze. Likewise, it is proposed to complement the conceptualization of natural resources by analyzing their links with the constitutional and fundamental right to enjoy a balanced and adequate environment.